New CUK–SEPIC converter based photovoltaic power system with hybrid GSA–PSO algorithm employing MPPT for water pumping applications - Priyadarshi, Neeraj; Bhaskar, Mahajan Sagar; Padmanaban, Sanjeevikumar; Blaabjerg, Frede; Azam, Farooque (IET power electronics, 2020)
This work proposes a CUK–SEPIC converter for photovoltaic water pumping application with maximum power point tracking (MPPT). For this a new hybrid gravitational search algorithm (GSA)–particle swarm optimisation (PSO) based MPPT method is proposed. The recent power electronics based CUK–SEPIC converter provides identical output with positive and negative ground reference. The novel converter minimises the ripple present in the supply current and provides optimum PV power extraction from solar module by integrating input and output magnetic cores of inductor. The proposed model is practically tested under changing solar insolation by employing switch reluctance motor for water pumping applications.